Measuring the quality of working life in the Ministry of Civil Service in Saudi Arabia - AlMutairi, Mouna Bint Jazza; AlDakhil, Haifa Bint Mansour (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aimed to identify the reality of the quality of work life in the Ministry of Civil Service from its staff viewpoint. The study relied on a descriptive survey method and used the questionnaire as a tool for the study، which contained six dimensions to measure the level of quality of work life. These dimensions are moral work environment conditions، job characteristics، wages and bonuses، working groups، supervision method، and the level of participation. The study society and sample consists of the Ministry of Civil Service in Riyadh staff of total (900) male and female employees. The questionnaires returned from the sample were 257 questionnaires. After a statistical analysis of the data using the statistical program SPSS، the study found a set of results. The most important result was that the quality of work life، from the viewpoint of staff، is considered moderate. In light of that، this study came out with a set of recommendations، including: the need to promote the concept of quality of work life in the work environment within the Ministry of civil Service، and increased staff opportunities to participate in decision-making، and the development of leadership skills for leadership of the heads of departments and managers in the ministry، and taking care of both the financial and moral incentives in addition to increasing training programs and scholarships of the Ministry of civil Service.